Effect of Application Intervals of Various Types of Insecticides in Controlling Fruit Fly (Bactrocera sp.) Pests on Production of Curly Red Chili (Capsicum annum L.) - Darmawansyah Darmawansyah; saripah ulpah; T. Edy Sabli (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2023)
The study's full title was "The Effect of Application Intervals of Different Types of Insecticides in Controlling Fruit Fly (Bactrocera sp.) Pests on Production of Curly Red Chili (Capsicum annum L.)." From July 2021 to October 2021, it was conducted in the dormitory area of the Riau Islamic University. The goal of this study was to ascertain how different vegetable insecticide kinds interacted with treatment intervals to control fruit fly pests and curly red chili plant production. This study employed a two-factor, entirely randomized design. The first factor was a combination of four different doses of pesticides, including isoprocarb 2 g/l, betel leaf extract 100 cc/l, neem leaf extract 100 cc/l, and lime leaf extract 100 cc/l. The application time interval, which has four levels—3 days, 6 days, 9 days, and 12 days—is the second element. 48 experimental units were created by combining 16 treatment combinations, each of which had three replications. There were 192 plants total because there were 4 plants per experimental unit and 2 plants were used as samples. The data is statistically analyzed before being subjected to the BNJ test. The outcomes demonstrated that not all parameters were affected by interactions and combinations of application intervals and different insecticide types, including the percentage of flowers to fruit, age at first harvest, fruit weight per plant, fruit weight per fruit, percentage of fruit flies attacked, other types of pests that attack, and age of disease across all treatments.